2020
DOI: 10.1111/cge.13858
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the genetic and phenotypic spectrum of the subcortical maternal complex genes in recurrent preimplantation embryonic arrest

Abstract: The subcortical maternal complex (SCMC) is an oocyte‐to‐embryo‐specific maternal functional module. Some variants of SCMC genes that contribute to preimplantation embryonic arrest have been identified. However, more novel variants should be identified to broaden the genetic and phenotypic spectrum of SCMC genes and establish their roles in embryonic development. We identified 13 novel variants in the SCMC genes, TLE6, NLRP5, NLRP2, and PADI6, from 10 of a total of 50 infertile females with recurrent preimplant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…Phenotypes of infertile women harboring biallelic TLE6 variants in this study are similar to the previously reported clinical cases [14,[23][24][25]. These four patients underwent a total of nine IVF/ICSI attempts in which the number of retrieved oocytes and frequency of oocyte maturity were not clearly abnormal; however, the fertilization rate and blastocyst development rate were very low.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Phenotypes of infertile women harboring biallelic TLE6 variants in this study are similar to the previously reported clinical cases [14,[23][24][25]. These four patients underwent a total of nine IVF/ICSI attempts in which the number of retrieved oocytes and frequency of oocyte maturity were not clearly abnormal; however, the fertilization rate and blastocyst development rate were very low.…”
Section: Discussionsupporting
confidence: 86%
“…Two of them obtained a very low number of low-quality embryos but failed to establish pregnancy [24]. Recently, using time-lapse imaging, Zheng et al found that the TLE6 missense variant c.1564G > C (p.Asp522His) is associated with direct cleavage (zygotes directly cleaved into more than two blastomeres) [25].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the incidence of TEL6 variants in our study is higher than other studies (Lin et al, 2020;Maddirevula et al, 2020). Furthermore, phenotypes of infertile women harboring biallelic TLE6 variants in this study are similar to the previously reported clinical cases (Alazami et al, 2015;Wang et al, 2018;Lin et al, 2020;Zheng et al, 2021). These four patients underwent a total of nine IVF/ICSI attempts in which the number and morphology of retrieved MII oocytes were not clearly abnormal.…”
Section: Discussionsupporting
confidence: 86%
“…Two of them obtained a very low number of low-quality embryos but failed to establish pregnancy (Lin et al, 2020). Recently, using timelapse imaging, Zheng et al (2021) found that the TLE6 missense variant c.1564G > C (p.Asp522His) is associated with direct cleavage (zygotes directly cleaved into more than two blastomeres).…”
Section: Discussionmentioning
confidence: 99%
“…Cytoplasmic maturation involves the occurrence of microscopic molecular processes, such as spindle assembly, organelle distribution and maternal mRNA decay 6–8. Several genetic factors associated with RPEA have been identified, such as spindle assembly molecular TUBB8 (MIM: 616768),9 10 subcortical maternal complex (SCMC) members, PADI6 (MIM: 610363),3 11 TLE6 (MIM: 612399)12 13 and NLRP5 (MIM: 609658) 14 15. However, pathogenic variants in the above-mentioned genes only account for approximately 20%–30% of the RPEA population,13 16 and the underlying genetic causes for other affected individuals remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%